To generate the equation we set up the factors
(x+3) * (x-1) * (x-2) which equals
x^2 + 2x -3 * (x-2)
x^3 +2x^2 -3x -2x^2 -4x +6 equals
x^3 -3x -4x +6 which equals
x^3 -7x +6
The answer is
x=10+2y
Steps:
2(x-2y)=20
x-2y=20/2 (in fraction form 20/2)
x-2y=10
X=10+2y
Answer:
B
Step-by-step explanation:
3(6)-5(-3)≥10
18-(-15)≥10
18+15≥10
33≥10
Answer:
1.3
Step-by-step explanation:
9 = 12
1= x
x= 1.3
Answer:
5.184 or 5.180 (rounded up)
Step-by-step explanation:
V = Bh or l x w x h
2.4 x 1.2 x 1.8 = 5.184 but rounded up would be 5.180